Uncertainty in Global Sourcing: Learning, Sequential Offshoring, and Selection Patterns - Mario Larch; Leandro Navarro (Center for Economic Studies and ifo Institute (CESifo), 2022)
We analyse firms' sourcing decisions under institutional uncertainty in foreign countries. Firms can reduce their uncertainty by observing offshoring firms' behaviour. The model characterises a sequential offshoring equilibrium path, led by the most productive firms in the market. With multiple countries, information spillovers drive sourcing location choices, leading to multiple equilibria with implications for countries' comparative advantages and welfare. Using firm-level data from Colombia, we test for the determinants and timing of offshoring decisions. We also derive spatial probit structural models to identify the firms' dynamic trade-off when they decide on the offshoring location. We find supportive evidence for the model's predictions.
Keywords: D81; D83; F10; F14; F23; 330; global sourcing; institutions; uncertainty; information externalities; learning; sequential offshoring; specialisation patterns; comparative advantages; survival analysis; transition analysis; spatial probit